The effects of acute respiratory illness on exercise and sports performance outcomes in athletes - A systematic review by a subgroup of the IOC consensus group on "Acute respiratory illness in the athlete" - Kaulback, K.; Pyne, D. B.; Hull, J. H.; Snyders, C.; Sewry, N.; Schwellnus, M. (European Journal of Sport Science, 2023)
Acute respiratory infections (ARinf) are common in athletes, but their effects on exercise and sports performance remain unclear. This systematic review aimed to determine the acute (short-term) and longer-term effects of ARinf, including SARS-CoV-2 infection, on exercise and sports performance outcomes in athletes. Data sources searched included PubMed, Web of Science and EBSCOhost, from January 1990 to 31 December 2021. Eligibility criteria included original research studies published in English, measuring exercise and/or sports performance outcomes in athletes/physically active/military aged 15-65 years with ARinf. Information regarding the study cohort, diagnostic criteria, illness classification and quantitative data on the effect on exercise/sports performance were extracted. Database searches identified 1707 studies. After full-text screening, 17 studies were included (n = 7793). Outcomes were acute or longer-term effects on exercise (cardiovascular or pulmonary responses), or sports performance (training modifications, change in standardised point scoring systems, running biomechanics, match performance or ability to start/finish an event). There was substantial methodological heterogeneity between studies. ARinf was associated with acute decrements in sports performance outcomes (four studies) and pulmonary function (three studies), but minimal effects on cardiorespiratory endurance (seven studies in mild ARinf). Longer-term detrimental effects of ARinf on sports performance (six studies) were divided. Training mileage, overall training load, standardised sports performance-dependent points and match play can be affected over time. Despite few studies, there is a trend towards impairment in acute and longer-term exercise and sports outcomes after ARinf in athletes. Future research should consider a uniform approach to explore relationships between ARinf and exercise/sports performance.